The general Code of Law join and military unit of Interior Troops, Ministry of Internal Affairs, Ukraine - Shmakov, О. М. (Honor and Law, 2019)
Offers the change to general Code of Law join and military part of Interior Troops, Ministry of Internal Affairs, Ukraine (general provisions, primary duty, function, organization of activity management joins and military units when performing the operative problems and decision of the administrative questions) represented.